Manajemen Risiko Pembiayaan Murabahah di BMT Amanah Ummah - Endro Wibowo (University of Darussalam Gontor, 2015)
This study aims to determine and analyze the process of murabahah financing risk management. Murabahah financing still dominates financing composition in sharia financial institutions, including BMT. BMT considers that murabahah financing process has a small risk so BMT expend more financing to this type. The composition of murabahah financing that is still very large in BMT and the existence of muamalah rules which states that